Cinema, the (Digital) Machine of the Imaginary: Revisiting Edgar Morin in the Quest to Create a Theory of Cinema in the Digital Age - Wade, Diana (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
Digital image technology facilitates the production and distribution of images, and at the same time, instills doubt as to the integrity of those images. As a result, spectators today trust and doubt the image while still retaining a need to see a double of the world on screen. Edgar Morin’s work on cinema permits us to speak of cinema in the digital age because he recognizes that from its origins cinema has been a “mirror-machine” that reflects the spectator’s imaginary and practical relationship with images as experienced through new technologies. I will explore Morin and Christian Metz’s writings on cinema to analyze cinema’s foundational element : the ability to satisfy the besoin de cinéma throughout changes in technology. Cinema persists as digital moving images because by evolving technologically it responds to the spectator’s need to see a double of the world on screen in order to negotiate the demands of society and personal desires.